Hospital Based Prevalence of Smoking Among Surgical Patients in Tertiary Care Hospitals of Karachi Pakistan - Nazir, Mohsin; Rehman, Azhar; Rashid, Saima; Salim, Bushra; Baig, Tanveer; Karam Khan, Karima (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the prevalence of smoking and to evaluate the knowledge about preoperative smoking cessation in patients coming for elective surgery. Method: The cross-sectional study was conducted from July 30, 2019, to March 17, 2020, in the preoperative anaesthesia assessment clinic and surgical wards of Aga Khan University Hospital, Civil Hospital Karachi, and Abbasi Shaheed Hospital, Karachi, and comprised all patients of either gender aged >12 years scheduled for elective surgery having American Society of Anaesthesiologists physical status I-IV. Data was analysed using Stata 13.. Results: Of the 811 patients, 478(59%) were male and 333(41%) were female. The overall mean age was 43.4±16.4 years and mean BMI was 25.0±5.8kg/m2. There were 164(20.2%) smokers in the sample. The overall knowledge about preoperative smoking cessation was significantly associated with the level of education and gender (p<0.05). Conclusion: Smoking in surgical patients was about one-fifth of the overall sample, and knowledge related to preoperative smoking abstinence was significantly associated with educational status and gender. Key Words: Prevalence of smoking, Surgical patients, Knowledge of smoking abstinence.